2019
DOI: 10.3390/ijerph16061077
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Algal-Bacterial Symbiosis in Wastewater Treatment

Abstract: In recent years, the algae-bacteria symbiotic system has played a significant role in the sustainable development of wastewater treatment. With the continuous expansion of research outputs, publications related to wastewater treatment via algal-bacterial consortia appear to be on the rise. Based on SCI-EXPANDED database, this study investigated the research activities and tendencies of algae-bacteria symbiotic wastewater treatment technology by bibliometric method from 1998 to 2017. The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…The analysis of the citations based on country demonstrated that these citations were interrelated and the countries with the least citations were Uganda and Nepal and as seen in the figure above, the citations in these countries were not correlated with the studies published in other countries. The purple rings in the above figure represent centrality (Liang et al, 2018;Qi, Chen, Hu, Song, and Cui, 2019;Chen, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the citations based on country demonstrated that these citations were interrelated and the countries with the least citations were Uganda and Nepal and as seen in the figure above, the citations in these countries were not correlated with the studies published in other countries. The purple rings in the above figure represent centrality (Liang et al, 2018;Qi, Chen, Hu, Song, and Cui, 2019;Chen, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The different colours in network structure depict temporal differences. The light-colored networks represent the more recent studies, while the dark networks represent the older ones (Chen, 2005;Ma, Wang, and Li, 2020;Qi, Chen, Hu, Song, and Cui, 2019). Thus, the studies depicted in yellow were the more recent studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the SCI-EXPANDED is not designed for bibliometric studies but for researchers to find published literatures [ 2 , 3 ]. KeyWords Plus collects repetitive terms within the references that the author(s) cited [ 4 ].…”
mentioning
confidence: 99%
“…Qi et al recently published an article in the journal, entitled “Bibliometric Analysis of Algal–Bacterial Symbiosis in Wastewater Treatment” [1]. The results presented in the original paper are not acceptable because of the use of inappropriate methods.…”
mentioning
confidence: 99%
“…Results by using searching keywords (alga* or microalga* or (*alga*-bacteri* and consorti*)) and (bacteri* or (activated and sludge)) and (wastewater or sewage) are the same as those from the original paper [1].…”
mentioning
confidence: 99%